Adolescents, parents, and providers' experiences of triadic encounters in paediatric diabetes clinics: A qualitative study - Imelda Coyne; Sinead Pembroke; Betsy Sleath; Maria Brenner; Edna F. Roche; Carol Hilliard; Declan Cody (Health Expectations)
Abstract Introduction Adolescents with Type 1 diabetes are a cohort whose self‐management of their diabetes care often declines during adolescence which can lead to adverse health outcomes. Research indicates that providers find it challenging to engage adolescents in communication exchanges during triadic encounters in diabetes clinics. Our study aimed to explore adolescents, parents, and providers' experiences of clinic encounters. Methods A qualitative study was conducted with a convenience sample of 13 adolescents with Type 1 diabetes (aged 11–17), 14 parents, and seven providers. Participants were recruited from two outpatient diabetes clinics in two urban children's hospitals, Ireland. Data were obtained using a combination of interviews and focus groups. Data were analysed thematically. Results Adolescents and their parents appeared to hold both positive and negative experiences of diabetes clinic encounters. Providers reported challenges associated with engaging adolescents in communication exchanges. The structure, focus and style of clinic encounters created barriers that potentially led to suboptimal adolescent participation and impaired provider–adolescent communication during clinic visits. Conclusions The findings provide insights into the challenges associated with adolescents' engagement in communication encounters in diabetes clinics. Healthcare providers could encourage adolescents to be more actively involved in their diabetes management, by taking an adolescent‐centred approach and creating a nonjudgemental milieu. Focusing on adolescent's agenda could lead to more meaningful and relevant discussions between providers and adolescents and ensure more tailored education in the time available. Adolescence is a risky period for nonadherence and adverse health complications; therefore, it is critical that providers make every contact count in diabetes clinic encounters. Patient or Public Involvement The study's design and delivery were guided by two advisory groups, comprising (1) five adolescents living with Type 1 diabetes (T1D) and (2) five parents of an adolescent with T1D.